2021
DOI: 10.12659/msm.928411
|View full text |Cite
|
Sign up to set email alerts
|

Gasdermin D Protects Mouse Podocytes Against High-Glucose-Induced Inflammation and Apoptosis via the C-Jun N-Terminal Kinase (JNK) Pathway

Abstract: Background The inflammation and apoptosis of podocytes contribute to the pathological progression of diabetic nephropathy. Gasdermin D (GSDMD) plays an executive role in pyroptosis, but its effect on high-glucose (HG)-induced inflammation and apoptosis remains unclear. The aim of this study was to investigate the effect of GSDMD on high-glucose-induced inflammation and apoptosis in podocytes. Material/Methods Mouse podocytes were cultivated by high- or normal-glucose me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The JNK pathway is an important regulatory pathway in apoptosis ( 27 ). Our results showed that Cdc42 induced the apoptosis of MPC5 cells partly through the JNK pathway, which is consistent with a previous study that demonstrated that gasdermin D knockdown attenuated HG-induced apoptosis by inhibiting the phosphorylation of JNK ( 26 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The JNK pathway is an important regulatory pathway in apoptosis ( 27 ). Our results showed that Cdc42 induced the apoptosis of MPC5 cells partly through the JNK pathway, which is consistent with a previous study that demonstrated that gasdermin D knockdown attenuated HG-induced apoptosis by inhibiting the phosphorylation of JNK ( 26 ).…”
Section: Discussionsupporting
confidence: 93%
“…JNK is a member of the mitogen-activated protein kinase superfamily, which can be activated by phosphorylation of the N-terminal Ser-63 and Ser-73 residues ( 25 , 26 ). The JNK pathway is an important regulatory pathway in apoptosis ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Disulfiram and NSA can directly affect GSDMD pore formation to inhibit pyroptosis [ 35 , 36 ]. In addition, GSDMD knockdown can attenuate high-glucose-induced inflammation and apoptosis in podocytes [ 37 ]. GSDME knockdown attenuated ATP-induced cell death and HMGB1 release in RAW264.7 cells [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…When caspase-11 is overexpressed, caspase-3 can also be activated to promote apoptosis ( Miao et al, 2018 ). Notably, transfection of podocytes with GSDMD siRNA reversed HG-induced inflammation and apoptosis, which may be related to the blocking of JNK signaling pathway ( Li et al, 2021a ). Although apoptosis-related proteins were also activated in caspase-3-dependent pyroptosis signaling pathway, pyroptosis activation occurred more rapidly ( Tsuchiya, 2021 ).…”
Section: Three Molecular Mechanisms Of Pyroptosismentioning
confidence: 99%